Radiofrequency ablation and related ultrasound‐guided ablation technologies for treatment of benign and malignant thyroid disease: An international multidisciplinary consensus statement of the American Head and Neck Society Endocrine Surgery Section with the Asia Pacific Society of Thyroid Surgery, Associazione Medici Endocrinologi, British Association of Endocrine and Thyroid Surgeons, European Thyroid Association, Italian Society of Endocrine Surgery Units, Korean Society of Thyroid Radiology, Latin American Thyroid Society, and Thyroid Nodules Therapies Association. Issue 3 (23rd December 2021) - Orloff, Lisa A.; Noel, Julia E.; Stack, Brendan C.; Russell, Marika D.; Angelos, Peter; Baek, Jung Hwan; Brumund, Kevin T.; Chiang, Feng‐Yu; Cunnane, Mary Beth; Davies, Louise; Frasoldati, Andrea; Feng, Anne Y.; et al.
Abstract: Background: The use of ultrasound‐guided ablation procedures to treat both benign and malignant thyroid conditions is gaining increasing interest. This document has been developed as an international interdisciplinary evidence‐based statement with a primary focus on radiofrequency ablation and is intended to serve as a manual for best practice application of ablation technologies. Methods: A comprehensive literature review was conducted to guide statement development and generation of best practice recommendations. Modified Delphi method was applied to assess whether statements met consensus among the entire author panel. Results: A review of the current state of ultrasound‐guided ablation procedures for the treatment of benign and malignant thyroid conditions is presented. Eighteen best practice recommendations in topic areas of preprocedural evaluation, technique, postprocedural management, efficacy, potential complications, and implementation are provided. Conclusions: As ultrasound‐guided ablation procedures are increasingly utilized in benign and malignant thyroid disease, evidence‐based and thoughtful application of best practices is warranted.